A Educação de Jovens e Adultos na perspectiva freireana: revisitando a experiência desenvolvida no município de Diadema - São Paulo - Fonseca, Maria Fátima da (2009)
This Master s dissertation integrates the cumulative research, within national reach, developed under the responsibility of Paulo Freire s Cathedra, from São Paulo Pontificia Universidade Católica (Catholic Pontificial University), coordinated by Professor Dr. Ana Maria Saul, denominated The presence of Paulo Freire in Brazilian Education: analysis of public systems teaching, since the 90 s. This research has the objective of analyzing the influence and contribution of freireano s thoughts in the Brazilian public teaching. The central objective of this work, herein presented, consists in investigating how Paulo Freire s referential, specifically the dialogism, the experience based knowledge , the vocation for the be-more , permeate the educational practice of Young Adults and Adults Education in Diadema City, São Paulo. A qualitative approach was chosen, using the analyses procedures of documents and field research, through observation and interviews. The organizer themes, which worked as a reference for the results analyses, were built from Paulo Freire s theoretical reference. They are the following: the classroom as a place for dialogue; the valorization of the learners experience based knowledge and the vocation for the be-more as a principle of an educational proposal. The results analysis and interpretation show that the defined freireanas categories have been concretized in the Education of Young Adults and Adults practices in Diadema City/SP and that the conditions for reinventing this education are given, in a permanent process of rethinking and reinventing, creating and innovating, day after day. This does not mean, however, that all problems are equated, but that there is a commitment for making a public education with social quality, which can contribute with the construction of a world where everybody is, indeed, a citizen